Dynamic proteome in enigmatic preeclampsia: an account of molecular mechanisms and biomarker discovery - Mary, Sheon; Patil, Gouri V.; Kulkarni, Asmita V.; Kulkarni, Mahesh J.; Joshi, Sadhana R.; Mehendale, Savita S.; Giri, Ashok P. (Proteomics Clinical Applications, 2012)
The coevolution of genomics and proteomics has led to advancements in the field of diagnosis and molecular mechanisms of disease. Proteomics is now stepping into the field of obstetrics, where early diagnosis of pregnancy complication such as preeclampsia (PE) is imperative. PE is a multifactorial disease characterized by hypertension with proteinuria, which is a leading cause of maternal and neonatal morbidity and mortality occurring in 5-7% of pregnancies worldwide. This review discusses the probable molecular mechanisms that lead to PE and summarizes the proteomics research carried out in understanding the pathogenicity of PE, and for identifying the candidate biomarker for diagnosis of the disease.
Keywords: Hypertension; Oxidative stress; Pregnancy complication; Proteinuria

Investigation of phosphoproteome in RAGE signaling - Batkulwar, Kedar B.; Bansode, Sneha B.; Patil, Gouri V.; Godbole, Rashmi K.; Kazi, Rubina S.; Chinnathambi, Subashchandrabose; Shanmugam, Dhanasekaran; Kulkarni, Mahesh J. (Proteomics, 2015)
The receptor for advanced glycation end products (RAGE) is one of the most important proteins implicated in diabetes, cardiovascular diseases, neurodegenerative diseases, and cancer. It is a pattern recognition receptor by virtue of its ability to interact with multiple ligands, RAGE activates several signal transduction pathways through involvement of various kinases that phosphorylate their respective substrates. Only few substrates have been known to be phosphorylated in response to activation by RAGE (e.g., nuclear factor kappa B); however, it is possible that these kinases can phosphorylate multiple substrates depending upon their expression and localization, leading to altered cellular responses in different cell types and conditions. One such example is, glycogen synthase kinase 3 beta which is known to phosphorylate glycogen synthase, acts downstream to RAGE, and hyperphosphorylates microtubule-associated protein tau causing neuronal damage. Thus, it is important to understand the role of various RAGE-activated kinases and their substrates. Therefore, we have reviewed here the details of RAGE-activated kinases in response to different ligands and their respective phosphoproteome. Furthermore, we discuss the analysis of the data mined for known substrates of these kinases from the PhosphoSitePlus (http://www.phosphosite.org) database, and the role of some of the important substrates involved in cancer, diabetes, cardiovascular diseases, and neurodegenerative diseases. In summary, this review provides information on RAGE-activated kinases and their phosphoproteome, which will be helpful in understanding the possible role of RAGE and its ligands in progression of diseases.
Keywords: Cell biology; Disease; Glycation; Kinase; Phosphoproteome; RAGE

Glycation inhibitors extend yeast chronological lifespan by reducing advanced glycation end products and by back regulation of proteins involved in mitochondrial respiration - Kazi, Rubina S.; Banarjee, Reema M.; Deshmukh, Arati B.; Patil, Gouri V.; Jagadeeshaprasad, Mashanipalya G.; Kulkarni, Mahesh J. (Journal of Proteomics, 2017)
Advanced Glycation End products (AGEs) are implicated in aging process. Thus, reducing AGEs by using glycation inhibitors may help in attenuating the aging process. In this study using Saccharomyces cerevisiae yeast system, we show that Aminoguanidine (AMG), a well-known glycation inhibitor, decreases the AGE modification of proteins in non-calorie restriction (NR) (2% glucose) and extends chronological lifespan (CLS) similar to that of calorie restriction (CR) condition (0.5% glucose). Proteomic analysis revealed that AMG back regulates the expression of differentially expressed proteins especially those involved in mitochondrial respiration in NR condition, suggesting that it switches metabolism from fermentation to respiration, mimicking CR. AMG induced back regulation of differentially expressed proteins could be possibly due to its chemical effect or indirectly by glycation inhibition. To delineate this, Metformin (MET), a structural analog of AMG and a mild glycation inhibitor and Hydralazine (HYD), another potent glycation inhibitor but not structural analog of AMG were used. HYD was more effective than MET in mimicking AMG suggesting that glycation inhibition was responsible for restoration of differentially expressed proteins. Thus glycation inhibitors particularly AMG, HYD and MET extend yeast CLS by reducing AGEs, modulating the expression of proteins involved in mitochondrial respiration and possibly by scavenging glucose. Significance: This study reports the role of glycation in aging process. In the non-caloric restriction condition, carbohydrates such as glucose promote protein glycation and reduce CLS. While, the inhibitors of glycation such as AMC, HYD, MET mimic the caloric restriction condition by back regulating deregulated proteins involved in mitochondria( respiration which could facilitate shift of metabolism from fermentation to respiration and extend yeast CLS. These findings suggest that glycation inhibitors can be potential molecules that can be used in management of aging. (C) 2017 Elsevier B.V. All rights reserved.

Possible role of glycation in the regulation of amyloid beta precursor protein processing leading to amyloid beta accumulation - Patil, Gouri V.; Joshi, Rakesh S.; Kazi, Rubina S.; Kulsange, Shabda E.; Kulkarni, Mahesh J. (Medical Hypotheses, 2020)
Alzheimer's disease (AD) is one of the most common forms of neurodegenerative diseases amongst the aged population. The disease is multifactorial, and diabetes has been considered as one of the major risk factors for the development of AD. Chronic hyperglycemic condition in diabetes promotes non-enzymatic protein modification by glucose termed as glycation, which affects protein structure and function. Previous studies have shown that many of the enzymes, including proteases, are affected by glycation. Conversely, glycated proteins are known to become resistant to protease action. In these hypotheses, we have extended these two concepts to the regulation of amyloid-beta protein precursor (A beta PP) by secretases leading to amyloid-beta (Af3) accumulation. The first hypothesis deals with the glycation of alpha-secretases leading to its reduced activity, while in the second hypothesis, A beta PP glycation may prevent a-secretases action, rendering its processing by beta secretase. As diabetes is a risk factor for the development of AD, either or both these pathways may operate, leading to the manifestation of AD.
Keywords: Alpha-secretase; Alzheimer `s disease; Amyloid-beta; Amyloid-beta protein precursor; Beta-secretase; Diabetes; glucose; Glycation; Type-3 diabetes